Penghitungan Beban Kritis pada Struktur Kolom Kontinu dengan Dua Bentangan akibat Pembebanan Secara Aksial - Eka Satria; Nusyirwan Nusyirwan; Muhammad Irfan (Department of Mechanical Engineering, Universitas Andalas, 2018)
This paper is aimed to determine the critical buckling load of continous column with two spans under axial loading. Firstly, the critical buckling loads is calculated theoretically based on concept of solid mechanic. The calculation is conducted for various ratio of L1/L2. This ratio shows a comparison of two span lengths. The used ratios in this calculation are L1/L2= 1/3,1/2, 2/3, 1/1, 3/2, 2/1, and 3/1. The critical buckling loads is calculated based on elastic analysis. For practical application, the results then are approached by regression technique of a least square method to find the best fit of design equation. Later, this equation is recommended as a practical equation in determining the critical buckling of continous column with two spans under axial loading.